Toy design - Uffelen, Chris Van. (Braun Publish,Csi, 2010)
Toys, fulfilling as they do one of mankind's most basic needs, have existed for as long as we have. From the earliest times both adults and children have used toys to simulate reality or simply to pass time. Renowned designers, artists and architects have always tried their hand at creating toys: from Frank Lloyd Wright's work with Frbel'S building blocks to Josef Hartwig's Bauhaus chess set that is still produced today. Gerrit Rietveld, Pablo Picasso, Marcel Breuer and Andy Warhol also designed toys. However, most often it was craftsmen and women$1 (Bsuch as the seamstress Margarete Steiff (Steiff teddy bears), the carpenters Christiansen (Lego), or the cabinet-maker Hans Beck (Playmobil)$1 (Bwho designed the most successful and enduring toys.s